Bos indicus introgression into (peri‐)alpine cattle breeds – evidence from the analysis of bovine whey protein variants. (16th June 2014) - Tetens, J. L.; Qanbari, S.; Drögemüller, C.; Pimentel, E. C. G.; Bennewitz, J.; Thaller, G.; Tetens, J.
Summary The major bovine whey proteins, α‐lactalbumin (α‐LA) and β‐lactoglobulin (β‐LG), exhibit breed‐specific genetic variation. The aim of this study was to identify possible new protein variants and determine the distribution of variants across a variety of 18 taurine and indicine cattle breeds applying a DNA‐based sequencing approach. To this end, the open reading frames of the respective genes (LALBA and LGB) were sequenced in 476 animals. Within the LALBA gene, a previously unknown synonymous and a previously undesignated non‐synonymous nucleotide exchange were identified. Furthermore, two known α‐LA variants (A and B) and four known β‐LG variants (A, B, C and W) were determined. The occurrence of typical indicine variants in some taurine cattle breeds, such as Suisse Eringer, German Hinterwälder and Hungarian Grey Steppe, further supports the hypothesis of ancient Bos indicus introgression into (peri‐)alpine cattle breeds.